Population Dynamics and Population Stabilisation, Draft Report of the Working Group Constituted by the Planning Commission in the Context of Formulation of Ninth Five Year Plan - Planning Commission (Planning Commission, 1996)
India with 2.5% of the world's land mass is the home of 1/6th of the world's population. The population of the country was 84.63 Crore in March 1, 1991 (1991 census) as against 68.33 Crore in 1981. Technological advances and improved quality and coverage of health care have resulted in rapid fall in mortality rates from 27 in 1951 to 9.3 in 1993. There had been increasing use of contraceptives over the same period, but the fall in birth rate, from over 40 in 1951 to 28.7 per 1000 in 1993 has been less steep; as a result the annual exponential population growth had been over 2 percent in the last three decades. The rapid increase in population has come in the way of improvement of quality of life of citizens in the country. Rightly, therefore, population stabilisation was recognised as one of tire six major objectives of the Eighth Plan. The Family PPWelfare launched in 1951 aims to deliver a package service for Family Planning and Maternal and Child Health through a country wide network of Primary Health Care System supported by secondary and tertiary care institutions linked by appropriate referral system.
Planning Commission
Planning Commission